Effect of WSi2 and Si3N4 contents on the thermal expansion behaviors of (Mo, W)Si2-Si3N4 composites. Issue 2 (1st February 2017) - Zhang, Houan; Lv, Jianxian; Zhuang, Shuxin; Chen, Ying; Gu, Siyong
Abstract: (Mo, W)Si2 -Si3 N4 composites with different contents of WSi2 and Si3 N4 as an oxidization resistance coating material of molybdenum substrate were fabricated by spark plasma sintering (SPS) and their thermal expansion behaviors were studied within a temperature range of 200–1400 °C in argon atmosphere. The phases and microstructures of the composites were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) equipped with energy-dispersive spectroscopy (EDS). The coefficients of thermal expansion (CTEs) of (Mo, W)Si2 -Si3 N4 composites decreased with increase of WSi2 content until 6 vol%, which was attributed to the effect of (Mo, W)5 Si3 phase content and grain size. However, the CTEs of the composites decreased with the increase of volume fraction of Si3 N4 . The relation between the volume fraction of Si3 N4 and the CTE of the composite was accordance with the Turner's model. The (Mo, W)Si2 -Si3 N4 composite with 6 vol% WSi2 and 30 vol% Si3 N4 showed a closer CTE to Mo substrate and a better thermal shock resistance.